Freshwater Discharge to Salt Lake and Its Implications for Freshwater Management at Rottnest Island, Western Australia - Anwar, Faisal; Wawn, P. (International Association for Hydro-Environment Engineering and Research (IAHR), 2013)
Rottnest Island (total area 2000 ha) is located 18 km off the coast of Western Australia and10% of its area is made up by salt lakes. The main freshwater supply at the island comes from two shallow unconfined aquifers. These aquifers may feed freshwater seepages along the lake edges which are important sources of freshwater for the fauna of the Island. Rottnest Island has experienced declining rainfall in recent decades, resulting in reduced recharge to shallow freshwater aquifers. Although desalination has replaced groundwater abstraction as the primary source of fresh water on the island, continued reductions in rainfall may have a devastating effect on island fauna. This paper investigates the impact rainfall has upon the salinity levels and discharge of a Rottnest Island aquifer, and was the first study to use variable density flow modeling to examine this relationship on Rottnest Island. This relationship was studied considering a critical cross section of the island which captured the largest cluster of freshwater seeps running along the northern salt lakes.The saline and freshwater interaction was modeled using the finite element model SUTRA. Simulations were performed for the next 20 years and the results support a direct association between reduced rainfall and a reduction in the thickness of the freshwater lens, reduced rates of discharge, and increased salinity levels in discharged water. The results revealed that the salinity level of water discharging near the surface after 20 years is predicted to vary between 0.24% and 1.18% at the extreme ends of the rainfall predictions of 900mm and 200mm respectively. The predicted increase of 1% to the salinity level will have a significant adverse effect based on the salt tolerance level of many species on the island. A reduction in rainfall is also predicted to reduce seepage water velocity at the aquifer discharge locations, with the model showing that a rainfall drop between 400-200mm over the next two decades will reduce this velocity by 15-30%. Results further revealed that if rainfall drops from its current yearly average of 600mm to 450mm, the thickness of the freshwater aquifer lens might shrink by 20% in the next two decades. The overall results suggest that decreases in rainfall due to climate change will reduce the availability of potable freshwater to fauna on Rottnest Island. Accordingly, it may be necessary to monitor a critical level at which potable water is insufficient for sustaining native fauna on the island, and supplement the water supply available in remote locations.